(untitled) (Window of Midwifery Journal, 2026)
Comprehensive care is a continuous and comprehensive midwifery service approach, covering pregnancy, childbirth, postpartum, newborn care, and family planning. This service is designed to meet the individual health needs of women and improve the quality of midwifery services. The goal of comprehensive care is to provide comprehensive and integrated care through an effective midwifery management approach. Mrs.“M” G3P2A0 with a gestation of 38 weeks and 5 days, with vital signs within normal limits and the mother’s physical condition normal. The mother delivered on January 24, 2025, at 16:15 WITA in good condition without complications. The baby was born spontaneously without abnormalities, weighing 2640 grams and measuring 48 cm in length. Postnatal visits were conducted twice at RSIA Masyita Makassar and once at home on Nipa Nipa Street, with the mother in good condition and vital signs within normal limits. Mrs. “M” plans to use an implant contraceptive device.